The Role Of The TPB In Predicting Sustainability Behavior In Educations - Aditya Pandu Wicaksono; Reny Lia Riantika; Riana Mahfuroh (Jurnal Reviu Akuntansi dan Keuangan, 2020)
The spirit of Sustainable Development Goals encourages people and institutions including universities to take an active role to attain the goals such as performing sustainable behavior. This research, therefore, is conducted to predict the factors underlying universities’ members to perform sustainable behavior by applying Theory of Planned Behavior. This study distributes an electronic questionnaire to 273 accounting undergraduate students in Universitas Islam Indonesia. All completed questionnaires were analysed by assistance from a statistic tool namely smartPLS version 3. This research discovers subjective norm does not significantly influence intention as well as sustainable behavior, however, the others influence significantly. Indirect test indicates that there are no mediation effects from intention variable in order to mediate the relation between three independent variables to sustainable behavior. This research argues that the insignificant influence of subjective norm to intention and sustainable behavior results insignificant influence of intention to sustainable behavior and generates no mediation effects.